THESISCOIN: CRYPTOCURRENCY TRANSACTION SCHEME TO OVERCOME MONEY LAUNDERING - THUFAILI IMDAD (NIM : 23216005), MUHAMMAD
The development of the current use of crypto currency began to shift from a medium of exchange to a financial investment. This is because the superiority of crypto currency in terms of security and transaction anonymity is key to money delivery. In addition, crypto currency guarantees more security standards because its mathematical assumptions are considered more difficult to manipulate the transaction. Currently some crypto-protocol protocols use special elliptic curves developed for the purposes of digital signatures in the software, such as curve25519 which, then secp256k1 used in the cryptto protocol Bitcoin and Ethereum. In this thesis, the application of elliptic curves in group signature schemes, from parameter selection in design and comparison. Then matters related to anonymity in the cryptographic scheme, especially the design of anonymity schemes are confined to the elliptic curve resulting from the implementation of group signatures. In general, the output of this research is the implementation of signature group signaling scheme based on elliptic curve cryptography on blockchain Ethereum. The resulting software aims to address money laundering using cryptofraphic schemes.